Analysis of the predictive variables of the intention to invest in a socially responsible manner. (20th September 2018) - Palacios-González, María Manuela; Chamorro-Mera, Antonio
Abstract: In recent years, socially responsible investment has acquired greater weight, for both individual and institutional investors. The segment of savers and investors worried about what is done with their money is growing. For this reason, financial institutions need to have a greater understanding of the characteristics and behaviours of these individuals. Most studies suggest that socio-demographic factors are not the fundamental difference between socially responsible investors and savers and conventional ones. Instead, the difference lies in attitudinal variables. However, we are aware of few studies to date that have analysed these variables. As a result, the purpose of this paper is to analyse the explanatory variables of the intention to invest in a socially responsible manner. A relationship model is proposed, according to which the intention to invest in a socially responsible manner can be explained by three variables: the socially responsible consumption of the individual, their perception of the personal gain and their perception of the effectiveness of the action. The analysis of the relationships was carried out using the Partial Least Squares technique. A survey was conducted involving 415 customers of financial institutions. According to the results, intention to invest in a socially responsible manner is explained by the three variables considered. The socially responsible consumption habits of the investor and the perception of the effectiveness attributed to the socially responsible investment have a direct and positive effect on intention. Whereas the perception of personal gain only has an indirect influence on intention, through the perception of the effectiveness of the action. These results allow financial and collective investment institutions to understand how to design their marketing strategies. Highlights: New investors take into account what is done with their money. Social responsible consumers are the most attractive target group for ethical banking. Intention to invest increases with the perception of the effectiveness of the action. Perception of personal gain only has an indirect influence on intention to invest.